Lower gastrointestinal endoscopic polypectomy: Cross-sectional study with 7503 consecutive endoscopic procedures - Başak, Fatih; Çalışkan, Yahya Kemal; Tilev, Sırma; Şişik, Abdullah (Journal of Surgery and Medicine, 2019)
Aim: Colonoscopic polypectomy is the most effective visceral cancer prevention tool in clinical medicine. Studies observed a 76-90% reduction in colorectal cancer incidence following colonoscopic polypectomy. We herein present a case series who underwent polypectomy by lower gastrointestinal system (GIS) endoscopy. Methods: The study population consisted of 7503 lower GIS endoscopy (colonoscopy or rectosigmoidoscopy) procedures performed in the Department of General Surgery between 2009 - 2019 for screening, diagnostic and follow-up purposes. 612 (8.2%) of the patients who underwent polypectomy were evaluated. The patients’ demographic data, clinical status, histopathology reports and follow-up findings were recorded. Results: During the study period, 612 patients (38 patients, twice and 3 patients, thrice) underwent polypectomy with lower GIS endoscopy. 386 of the patients were male and 226 were female. The mean age of the patients was 57.3 (13.7) (range 24-89) years. A total of 813 polypectomies were performed, and 118 procedures included two or more polypectomies. The most common sites of polypectomies were rectum (n=233, 29.5%), sigmoid colon (n=208, 25.3%) and the descending colon (n=107, 13%). Histopathological examination revealed 25 adenocarcinomas (4.1%), 98 high grade dysplasias (16%) and 269 low grade dysplasias (44%). In terms of histopathological results, there were no significant differences between genders (p=0.098), however, younger patients (mean age: 51.7 years (14.7)) were more likely to have benign results and malignity was more often encountered in older patients (p<0.001). The mean ages of patients with adenocarcinoma and high-grade dysplasia were 61.2 (12.1) and 63.6 (11.1) years, respectively. Necessary treatments and follow-ups were performed for the related pathologies. Conclusion: We observed that 8.2% of the patients undergoing lower GIS endoscopy had polyps and 20.1% of these polyps needed additional treatment, and 44% needed follow-up colonoscopy control. It should be noted that patients with various lower gastrointestinal tract symptoms may have malign polyps, potentially curable by polypectomy.